Co-axial electrospinning of liposomal propolis loaded gelatin-zein fibers as a potential wound healing material - ŞAHİN, ALİ (My University, 2023)
In this study, propolis extract (PE) was first encapsulated in different liposomal formulations (65–370 nm) with high encapsulation efficiency (68%–93%). The liposomal PE was further embedded in a food-grade gelatin-zein core/shell fiber by using the co-axial electrospinning method. Transmission electron and confocal laser scanning microscopy verified the structure of liposomes and their homogeneous dispersion in fibers. Scanning electron microscopy (SEM) images confirmed the smooth morphologies of core/shell liposomal fibers. The loading of PE in liposomal fibers improved both thermal (differential scanning calorimetry) and textural (elongation at break and tensile strength) properties, and the fibers loaded with more PE provided higher mucoadhesiveness. The PE-loaded fiber showed higher antimicrobial activity against Staphylococcus aureus. The incorporation of liposomal PE in fiber enhanced the viability of human skin fibroblast (HFF-1) cells. The adhesion of HFF-1 cells on fiber was demonstrated by SEM, thus PE-loaded liposomal fiber could provide an efficient platform for cell growth. The findings of this study proposed that propolis-loaded liposomal hybrid fibers produced by the co-axial method can be used as a potential wound healing material.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; KİMYA, FİZİKSEL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; POLYMER SCIENCE; CHEMISTRY, PHYSICAL; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya; Fizik Bilimleri; Yüzeyler, Kaplamalar ve Filmler; Polimerler ve Plastikler; Malzeme Kimyası; General Chemistry; Physical Sciences; Surfaces, Coatings and Films; Polymers and Plastics; Materials Chemistry; cell adhesion; encapsulation; HFF-1; lecithin; mucoadhesion; nanofilm; cell adhesion; encapsulation; HFF-1; lecithin; mucoadhesion; nanofilm